Strengthen Integrity in Human Resource Management: The Application of Professional Ethics in The Digital Era - Layla Qodri Ani; Rizky Fajar Hermansyah; Ashil Andy Hakim; Nadia Rahmadhani; Amanda Khoirun Nisa; Amanda Gheanisa Lutfi; Arief Budiono (Proceeding International Conference Restructuring and Transforming Law, 2024)
This research highlights the importance of building integrity in human resource management through the application of the ethics of the civil service profession in the digital era. It includes a summary of the background of the problem, research objectives, and relevance of the topic in the current context. This research uses a qualitative approach with data collection techniques through in depth interviews and participatory observation. The data analysis method involves a process of coding and theming to identify patterns and trends emerging from t he data. This article makes a novel contribution by highlighting how integrity in human resource management can be strengthened through the implementation of professional civil service ethics in the digital age. It distinguishes itself from previous research by exploring the impact of recent digital technologies on Human Resource management practices and professional ethics. This research reveals findings that illustrate the important role of professional personnel ethics in building organizational integrity. Discussions include the implications of the findings for effective Human Resource management practices in the digital era and efforts to address challenges related to integrity. The integration of professional ethics in human resource management emerged as a key strategy to strengthen organizational integrity in the digital era. The conclusions of this study provide an overview of the practical implications and directions for further research in this domain.